Natural-Convection Phenomenon from a Finned Heated Vertical Tube: Experimental Analysis - Shehab, Saad Najeeb (Al-Khwarizmi Engineering Journal, 2019)
In this work, an experimental analysis is made to predict the thermal performance of the natural-convection phenomenon from a heated vertical externally finned-tube to surrounding air through an open-ended enclosure. Two different configurations of longitudinal rectangular fin namely, continuous and interrupted are utilized with constant thickness, different numbers, and different heights are extended radially on the outer surface of a heated tube. The tube is heated electrically from inner surface with five varied power input magnitudes. The effect of fins configuration, fins number, fins height, and heat flux of the inner tube surface on the thermal performance of natural convection have been studied and analyzed experimentally. Obtained results show that the tube with twelve interrupted longitudinal fins gives the best natural-convection thermal performance in terms of average Nusselt number, about 20% greater than that for the tube with continuous fins. Experimental correlations to predict the average Nusselt number for the heated tubes with continuous and interrupted longitudinal fins are proposed. The present data are compared to previous study and good convergence is noticed.